The Judge's Consideration of the Defendant's Statement in Imposing a Sentence Against the Security Guard While on Duty - Neni Vesna Madjid; Rachmat Akbar (Master of Law Program, Ekasakti University, 2023)
In Article 184 Paragraph (1) of Indonesian Criminal Code (KUHAP) it is stated that a defendant’s testimony in a trial is not sufficient to prove that the defendant has been guilty of committing a criminal offense without being supported by other evidence. There are various forms of consideration of the judge against the defendant’s testimony in criminal sentencing by the security guard on duty in the Decision Number: 372/Pid.B/2022/PN.Pdg and Decisions Number: 373/Pid.B/2022/PN.Pdg. The issues being studied are First, How is the judge’s consideration of the defendant’s testimony in criminal sentencing by a security guard on duty. (On the Decisions Number: 372/Pid.B/2020/PN.Pdg and Number: 373/Pid.B/2020/PN.Pdg)? Second, How is the judge’s decisions based on the consideration of the defendant’s testimony in criminal sentencing by a security guard on duty. (On the Decisions Number: 372/Pid.B/2020/PN.Pdg and Number: 373/Pid.B/ 2020/PN.Pdg)? This study is analytical descriptive research. The approach used in this study was normative juridical approach. The data used in this study were secondary data. All data and materials obtained from the results of the study were prepared and analyzed qualitatively, and presented in a descriptive qualitative form. Based on the results of discussion and analysis it can be concluded that. First, That the judge’s Consideration of the Defendant’s Testimony in Criminal sentencing by the Security Guard on Duty on the Decisions Number: 372/Pid.B/2020/PN.Pdg and Number: 373/Pid.B/2020/PN.Pdg has covered both juridical and non-juridical considerations. Second, That the decision of the judge Based on Consideration of The Defendant’s Testimony in criminal sentencing by the Security Guard on Duty on The Decisions Number: 372/Pid.B/2020/PN.Pdg and Number: 373/Pid.B/2020/PN.Pdg is based on the defendant’s evidence and aligned with other evidence such as witness testimony and letters.